Un’analisi sociologica della violenza di genere attraverso il cinema italiano - Fornari, Silvia; Curti, Sabrina (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2020)
The essay analyzes the phenomenon of gender violence through films and documentaries in Italy. As Edgar Morin teaches, there is indeed a close intersection between movie and sociology. Movie, as a game of refraction of the real and the imaginary, makes it possible to investigate the phenomenon of gender violence from the point of view of history and life stories, with a sociological view that intertwines historical, political, cultural and social aspects. and relational. The movie, as well as having a broad and extensive educational value, is a useful method of knowledge to investigate the socio-cultural representation of the masculine and feminine, as well as the relationship between masculine and feminine. The objectives that we intend to pursue are therefore essentially two: on the one hand, we will analyze the representation of socio-cultural models of men and women, through the main Italian documentary films from the 1960s to today: Comizi d’amore di P.P. Pasolini (1964), D’amore si vive by S. Agosti (1984), Vogliamo anche le rose by A. Marazzi (2007), Oggi insieme domani anche by A. De Lillo (2013); on the other hand, the representation of the phenomenon of gender-based violence will always be considered in Italian films from the 1960s to today, with particular attention to those who have recently been selected and disseminated on the web by the various Italian associations that deal with the phenomenon: Sedotta e abbandonata by P. Germi (1964), Il branco by D. Risi (1994), Primo amore by M. Garrone (2004), Un giorno perfetto by F. Ozpetek (2008).